Determining Chronic Cough Using the Methacholine Bronchial Provocation Test - Esra Arslan Aksu; Oğuz Uzun (Jurnal Respirasi)
Introduction: Chronic cough is a common symptom in pulmonology outpatient clinics, often associated with lung conditions, though extrapulmonary causes can also be responsible. This study aimed to detect bronchial hyperreactivity (BHR) and cough-variant asthma using a methacholine bronchial provocation test (BPT) in patients with chronic cough for whom standard diagnostic procedures could not identify a cause.